Crepidium sect. Crepidium (Orchidaceae, Malaxidinae)—Chemical and Morphological Study of Flower Structures in the Context of Pollination Processes - Hanna B. Margońska (MDPI AG, 2021)
Crepidium is a large genus of mainly pantropical orchids. The lips of its flowers are upwardly directed and do not serve as landing platforms for pollinators. This role is assumed by the dorsal sepal and/or gynostemium. Information about the pollination and floral morphology of this genus is scarce. To date, no papers have been published on these topics. Field observations have revealed that the flowers are visited by small flies, midges, fruit flies, other small dipterans, ants, spiders, and mites. Preliminary observations revealed at least two forms of small liquid droplets secreted on the lip surface of Crepidium species: simple secretions from epidermal cells, and cell sap released upon the rupturing of raphide-producing cells. Further research revealed that this was the first time liquid secretion was recorded in this genus. Floral secretions were subjected to sequential organic solvent extraction and gas chromatography–mass spectrometry (GC–MS). Floral parts were investigated by means of scanning (SEM) and transmission electron microscopy (TEM), and histochemical tests. The presence of liquid droplets on the lip of Crepidium, the presence of a food reward, and the sequence of raphide development are reported here for the first time.